Topik Modeling Penelitian Dosen JPTEI UNY Pada Google Scholar Menggunakan Latent Dirichlet Allocation - Nurlayli, Akhsin; Nasichuddin, Moch. Ari (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2019)
The mapping of research topics for lecturers is necessary to determine the research tendencies in a department or study program. This study aims to implement topic modeling in the publication titles of the Department of Electronics and Informatics Education Engineering of Universitas Negeri Yogyakarta (JPTEI UNY) lecturers taken from Google Scholar. The method used for topic modeling is the Latent Dirichlet Allocation (LDA). LDA is a generative probabilistic model for finding the semantic structure of a corpus collection based on the hierarchical bayesian analysis. After the topic modeling process, the results showed that JPTEI UNY lecturers tend to have four research clusters consisting of vocational education, system development, learning media, and vocational learning systems.